Propagation of elastic waves in DNA - Sunil Mukherjee; Saumyendra Nath Sarkar; Probhas Raychaudhuri; Sunil Kumar Mazumdar (International Journal of Mathematics and Mathematical Sciences)
The mathematical analyses of longitudinal and torsional elastic waves transmitted along DNA molecule undergoing Brownian motion in solution are presented. Longitudinal vibrations in DNA are shown to be responsible for drug intercalation and breathing. The near neighbor exclusion mode of drug intercalation is explained. Torsional oscillations in DNA are shown to be responsible for conformation transitions from a right handed to a left handed form, depending on sequence specificity in high salt concentration.